“I am air and fire...”: On the Interpretation of Anna Akhmatova’s Poem Cleopatra - Mikhailova, Galina (Literatūra, 2024)
In interpreting Akhmatova’s poem Cleopatra, attention is often primarily given to its historical and social parameters, which are involved in the poem’s meaning-making process. This article suggests focusing on the literary sources of the poem (Shakespeare’s tragedy Antony and Cleopatra and Horace’s ode), exploring Akhmatova’s working notes, different versions of the lyrical heroine in her poetry, as well as the reproduction of her image in poems dedicated to her, testimonies of memoirists, essays, and philological observations of Akhmatova’s contemporaries. In this case, the poem may be read within the framework of the poet’s intimate relationship with ‘being’, and it may turn out to be a space for the embodiment of the author’s essential personal characteristics.